RATIO LEGIS KEPUTUSAN BERSAMA ENAM LEMBAGA NEGARA TENTANG LARANGAN KEGIATAN DAN PENGGUNAAN SIMBOL/ATRIBUT FPI RATIO LEGIS OF THE JOINT DECISION OF SIX STATE INSTUTIONS REGARDING THE PROHIBITION OF FPI ACVITIES AND USE OF ITS SYMBOLS AND ATTRIBUTES - Vioni Akse, Ellin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
This research is propted by Law Number 30 of 2014 concerning Government Administration. The object of study in this paper is focused on the discussion of the Legis Ratio of the decree made by the Republic of Indonesia’s Minister of Home Affairs, Minister of Law and Human Rights, Minister of Communication and Information, Attorney General, and the Head of the National Counter-Terrorism Agency, Number 220-4780 of 2020, Number M.HH-14.HH.05.05 of 2020, Number 690 of 2020, Number 264 of 2020, Number KB/3/XII/2020, Number 320 of 2020 concerning the Prohibition of Islamic Defender’s Front (FPI) activities and use of its symbols and attributes. This study is intended to analyse the Legis Ratio of the Joint Decisions made by the Six State Institutions that meet the legal conditions of the decision and its legal effects.The result of this study shows that the decrees of the Six Institutions are not in accordance with the reasons for consideration and the purpose of the FPI Decree towards the necessity to contain the reasons for juridical, sociological, and philosophical considerations as a ratio legis in deciding. In addition to that, the decrees do not meet the legal requirements of a decision on the element of authority which make the legal effects invalid hence the legal effects are non-binding since the decision was made. This means that all legal effects that have arisen from the decree are considered to have never existed and are deemed to not fulfil the elements of procedure and matter hence its legal effects are not binding from the time they are revoked or remain valid until the revocation is made.